HIV infection modulates IL‐1β response to LPS stimulation through a TLR4‐NLRP3 pathway in human liver macrophages. Issue 4 (18th February 2019) - Zhang, Lumin; Mosoian, Arevik; Schwartz, Myron E.; Florman, Sander S.; Gunasekaran, Ganesh; Schiano, Thomas; Fiel, M. Isabel; Jiang, Wei; Shen, Qi; Branch, Andrea D.; Bansal, Meena B.
Abstract: IL‐1β is an important mediator of innate inflammatory responses and has been shown to contribute to liver injury in a number of etiologies. HIV patients have increased necroinflammation and more rapid fibrosis progression in chronic liver injury compared to non‐HIV‐infected patients. As the resident liver macrophage is critical to the IL‐1β response to microbial translocation in chronic liver disease, we aim to examine the impact of HIV‐1 and LPS stimulation on the IL‐1β response of the resident hepatic macrophages. We isolated primary human liver macrophages from liver resection specimens, treated them with HIV‐1BaL and/or LPS ex vivo, examined the IL‐1β response, and then studied underlying mechanisms. Furthermore, we examined IL‐1β expression in liver tissues derived from HIV‐1 patients compared to those with no underlying liver disease. HIV‐1 up‐regulated TLR4 and CD14 expression on isolated primary CD68+ human liver macrophages and contributed to the IL‐1β response to LPS stimulation as evidenced by TLR4 blocking. Nucleotide‐binding domain, leucine‐rich‐containing family, pyrin domain‐containing‐3 (NLRP3) was shown to be involved in the IL‐1β response of liver macrophages to HIV‐1 infection and NLRP3 blocking experiments in primary CD68+ liver macrophages confirmed the contribution of the NLRP3‐caspase 1 inflammatory signaling pathway in the IL‐1β response. High in situ IL‐1β expression was found in CD68 + cells in human liver tissues from HIV‐1‐infected patients, suggesting a critical role of IL‐1β responses in patients infected by HIV. HIV infection sensitizes the IL‐1β response of liver macrophages to LPS through up‐regulation of CD14 and TLR4 expression and downstream activation of the NLRP3‐caspase 1 pathway. These findings have implications for enhanced immune activation in HIV + patients and mechanisms for rapid fibrosis progression in patients with chronic liver injury. Abstract : Resident liver macrophages infected by HIV‐1 demonstrate an increased IL‐1β response to LPS that is mediated by TLR4 and downstream activation of the caspase1‐NLRP3 pathway.